O desafio de educar para valores do séc.XXI - Baltazar, Isabel (2018)
This qualitative study came to exist before the need to take action in face of the crisis of values that is felt nowadays. Its main purpose is to understand how values are transmitted to children as well as the role of family and school before such a task. The research was based on documentary collection and real testimonies of individuals who we felt were beneficial to the study. We have chosen these two methods of gathering information in order to build on in real stories and experiences, while supported by reference authors. Throughout the study fundamental concepts will be presented, such as values, family and school, framed in their specific fields of analysis, using educators’ interviews that demonstrate the conceptual point of view that was the starting point for the theoretical framework of the theme. All of the research took place in order to answer the following research questions: "What is the role of school and family towards the education for values?"; "What is the current reality of education for values?"; "What is the challenge of the teacher in face of the current reality?" It was demonstrated that family and school are key institutions in the transmission of values, although the crisis of values in families increasingly transfers to the school the responsibility of education for values.